FIFO and global production networks: Exploring the issues - Rainnie, Alistair; Fitzgerald, Scott; Ellem, Bradon; Goods, Caleb (National Institute of Labour Studies, 2014)
In this introductory article, we provide a context for subsequent articles in this special edition. We do not intend to provide a comprehensive overview of the costs and benefits of FIFO. This ground is covered in other articles here (see also Morris 2012). We argue that FIFO represents the third wave in a series of spatial fixes, whereby resource companies mining in far north Western Australia sought to manage relationships between themselves, their workforces, and the communities in which these workers live. We are responding to the demands of Coe (2013) and Kelly (2013) who wish to see Global Production Network analysis move beyond a narrow workplace focus to incorporate issues such as environmental landscapes, households and livelihoods, and social and spatial unevenness of development. In so doing, we develop the form of analysis of GPNs, labour; and uneven development outlined in Rainnie et al. (2011; 2013)